Perder tudo para tudo ganhar: O relato do aniquilamento paulino por CRISTO em Filipenses 3,7-14 - Veras Pereira, Paulo de Tarso (Kairós: Revista Acadêmica da Prainha, 2021)
Try to see the transformation of the apostle Paul and his radical annihilation by Christ into a narrative contained in the Epistle to the Philippians, notably in the perícope in 3,7-14. Understand in the examination of the text the kenosis Pauline, its total dispossession by the one whom it persecuted. Understand how the unexpected event in Damascus marked the turnaround in the life of the Tarsus Jew. Meeting Jesus of Nazareth transmuted his existence. Give it all, for everything to have. The apostle's renouncing action fits in with the stripping example of Christ. Paul's emptying stems from the blunt reflection of the servitude of Jesus Christ. Everything he had in mind turned into a convinced loss. Here the title of the article is endorsed, Paul, with crystal clear lucidity, chose to “lose everything, to win everything”.